Beyond imposex: other sexual alterations in a nassariid snail from Patagonia - Narvarte, Maite Andrea (2017)
The occurrence of a penis in female gastropods has commonly been accepted as an indicator of tributyltin (TBT) pollution. During the surveys performed in Patagonian waters between 2002 and 2010, individuals of Buccinanops deformis with a short penis and an external vas deferens were initially considered as showing imposex. Doubt arose when different manifestations of the phenomenon were identified at the two sites with the densest populations of the species (San Antonio Bay, SAB, and Villarino). This led us to search at both locations for: (a) histological confirmation of sex, (b) butyltin measurements in sediments and snail tissues, and (c) incidence of trematode infestation. We found that both populations have individuals with a short penis. While all the inspected individuals from SAB were histologically identified as females (imposex), those from Villarino were identified as males. Trematodes were absent in individuals from SAB and showed very low prevalence in those from Villarino, with metacercariae found in the digestive gland. In snail tissues, butyltins were found mainly in the form of dibutyltin (DBT) in SAB and at negligible levels in Villarino. In sediments, butyltins were found only in the form of TBT, at higher levels in SAB than in Villarino. Thus, it became clear that our finding of a short penis is a manifestation of imposex on females from SAB related to the high TBT levels, whereas in Villarino it is a male trait, which is not related to TBT or a trematode infestation but may be a Dumpton syndrome-like abnormality.